VLSI Design and Test 17th International Symposium, VDAT 2013, Jaipur, India, July 27-30, 2013, Revised Selected Papers - Gaur, Manoj Singh; Zwolinski, Mark.; Laxmi, Vijay; Boolchandani, Dharmendra; Sing, Virendra; Sing, Adit D.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 17th International Symposium on VLSI Design and Test, VDAT 2013, held in Jaipur, India, in July 2013. The 44 papers presented were carefully reviewed and selected from 162 submissions. The papers discuss the frontiers of design and test of VLSI components, circuits and systems. They are organized in topical sections on VLSI design, testing and verification, embedded systems, emerging technology.
VLSI design -- Testing and verification -- Embedded systems -- Emerging technology.
Keywords: Computer science; Computer hardware; Computer Communication Networks; Computer Science; Computer Hardware; Processor Architectures; Computer Communication Networks